Good dog, Aggie - Ries, Lori.; Dormer, Frank W. (Watertown, MA : Charlesbridge, 2009)
When Aggie the dog does not mind, Ben takes her to obedience school which ends in disaster, but while practicing at home one day Ben realizes what really motivates Aggie to mind.
1.3
K-3
Keywords: Dogs -- Juvenile fiction; Dogs -- Training -- Juvenile fiction; Obedience -- Juvenile fiction; Pets -- Juvenile fiction; Dogs -- Fiction; Dogs -- Training -- Fiction; Obedience -- Fiction; Pets -- Fiction; Dogs -- Fiction; Dogs -- Training -- Fiction; Obedience -- Fiction; Pets -- Fiction